Indonesian EFL Teachers' Perspectives on AI for Lesson Planning - Dini Dwi Rahayu; Hana Prameswari Suherni; Muhammad Sultan Al-Ma’mun; Fadhillah Awthar Alkahfi; Hamid, Farida; Faridah (Universitas Islam Negeri Raden Intan Lampung, 2025)
For a long time, teachers are being burdened with their abundance of never-ending workload that could cause exhaustion. One of those workloads that is necessary for teachers to do is lesson plan. With the recent development in AI tools technology, it promised to be capable in easing the teacher’s burden creating lesson plans, albeit the teachers are willing to implement it. Hence, this study aims to find an EFL teacher’s perspective on utilizing AI tools in their lesson plan. By using Technology Acceptance Model (TAM), This preliminary study utilized a purposive sample of 20 EFL teachers at UIN Syarif Hidayatullah Jakarta. While the sample size is modest, it serves as an exploratory pilot to identify immediate trends in teacher attitudes during the rapid introduction of AI tools in the 2024/2025 academic year. The findings provide a foundational baseline for future large-scale longitudinal research on AI adoption in Indonesian secondary schools. The study findings indicate that teachers agree that AI tools are useful (M=3.32), easy to use (M=3.44), exhibit positive attitude (M=3.40), and strong behavioral intention towards using (M=3.30). The findings of this study hopefully contribute to a better perspective of implementing AI tools in EFL teacher’s lesson plan and convince other teachers to perceive a similar acceptance. Furthermore, the insight also provides a useful reference for future research that wants to develop their research in this certain topic.